PENGELOLAAN KEUANGAN DESA DI DESA JEMBRAK KECAMATAN PABELAN KABUPATEN SEMARANG - dyah palupiningtyas; Toni Sunaryadi Sunaryadi; Heru Yulianto (Universitas Sains dan Teknologi Komputer, 2021)
This study attempts to describe how the stages of planning in village financial management in Jembrak Village in Pabelan District, Semarang Regency. This research was carried out because of the phenomenon in the field which showed that the delivery of APB Village from the village to the District still often experienced delays. This research method is descriptive with a qualitative approach. The informants of this study consisted of 5 village employees in the Jembrak Village District, Pabelan District and the village administration. Data collection techniques used in the form of interviews, observation, and documentation. Data analysis was performed by data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Jembrak Village in the District of Pabelan District has carried out a plan in managing village finances quite well in accordance with the stages set by applicable regulations. The local government has conducted socialization related to regulations, providing training, assistance and supervision. The village has developed a village RPJM that is aligned with the Semarang Regency RPJMD. The village medium term development plan is then set out in the village RKP which is used as the basis for preparing the village budget. In the process of making the village medium term development plan and the village RKP, the village has involved village institutions and the local village community to play an active role. However, there are still some weaknesses that need to be fixed. The main weakness that must be corrected is the quality of human resources in this case village officials. The number of village assistants with only 3 people to handle 17 villages also became an obstacle related to coordination and assistance in the village. For 2017 the village government felt greatly helped by the use of the siskeudes. With the use of the siskeudes, the planning stage through to accountability becomes more organized.Keywords: Management, Finance, Village